Distributed Renewable Generation and Power Flow Control to Improve Power Quality at Northern Senja, Norway - Jacobsen, Tobias Thørnquist (UiT The Arctic University of Norway, 2019)
Distributed renewable generation and power flow control are promising tech- nologies for increasing power system efficiency. Renewable energy production close to consumption reduces need for transport of power to these locations. The benefits of reactive flow control are well documented, and in recent years the use of energy storage for active power control has increased in relevance. The power system at Senja in northern Norway is suffering from limited trans- fer capacity, and the energy demand is expected to increase in coming years. In this thesis, the performance of distributed renewable generation and power flow control is evaluated. The potential production of solar and wind energy systems at the island is quantified through simulations, and the effect this production can have on network performance is discovered. Shunt capacitors for reactive power compensation, and energy storage systems for peak load shaving are also evaluated in terms of network performance. A good potential for renewable generation is found, especially for wind. It is found that 20 % of the bottleneck feeder load can be released as a result of renewable generation, which limits requirements for hydro production. However, the main feeder will become overloaded with increasing demand, even with the addition of renewable generation. Implementation of power flow control measures shows promising results, enabling a reduction of 30-50 % in voltage drops during heavy load in the distribution network. Network losses are also reduced, which indicates that the network operates more efficiently. From these results, it is evident that the components considered will have the possibility to enhance network performance. Based on these observations, additional topics to be analyzed in further work is proposed.